Knowledge of the Artisanal Fishermen of Casma: An Ethnographic Perspective - Pastor Seperak, Marly Mahly (2025)
This article presents the results of a qualitative research project with an ethnographic approach based on interviews and observation of the work of artisanal fishers in Casma, a small coastal town in northern Peru. It explores the worldview, work techniques, and the changes, difficulties, and challenges faced by this fishing community. The study reveals how fishers perceive the sea as a living entity governed by spiritual norms and ritual practices; Furthermore, the fishers' technical language reflects their experience and the intergenerational transmission of knowledge. All of this allows us to understand how these elements shape a local knowledge that articulates experience, tradition, and adaptation to changes in fishing activity. It also highlights the importance of documenting and valuing this local knowledge as part of intangible cultural heritage